Analisis Dan Perancangan Sistem Informasi Layanan Kepuasan Mahasiswa Pada Universitas Adiwangsa Kota Jambi - Dauli, Rd. Rahmat; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2021)
Student satisfaction services at Adiwangsa University, Jambi are currently done manually by filling out a questionnaire in paper form. One of the crowds found during this process was the relatively long time for the compilation of the questionnaire results. To facilitate the process of filling out the questionnaire carried out by students, a website page is needed as a student satisfaction service information system that can manage the summary of the questionnaire results properly and quickly. This study aims to design a prototype of the performance information system for lecturers and educational staff at Adiwangsa University Jambi. This information system design uses the servqual method and the unified model language (UML) to describe the information system prototype design.